Community Perception on Waste in Koto Tangah District - Ernawati, Ernawati (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This study aims to find out how the public perception about waste and the factors that influence perception. This type of research is survey research, with a population of people in Koto Tangah District, Padang City. The research sample was taken based on population density assuming the amount of waste produced was influenced by the population. Based on the results of the study, it is known that 68% of the people have a low perception of waste with the view that waste is a useless waste, has no economic value, and must be disposed of immediately; and 32% of the community has a moderate perception with the view that some waste has economic value and can be reused. Factors that influence people's perceptions of waste management are understanding and knowledge, concern for the environment and the willingness to process waste into products which have economic value. Community knowledge about waste management is high about sorting and processing waste, but people have a social environment that seldom uses waste and seldom participates in counseling on how to use waste, so that public awareness of the environment, confidence in processing waste and the willingness to process waste become products that have economic value is also low.